Toksisitas Biji Srikaya Terhadap Kumbang Tepung (Tribolium Castaneum) Pada Gandum - Subagiya Subagiya; Ato Sulistyo; Umi Nurchasanah (Universitas Sebelas Maret, 2018)
Wheat (Triticum aestivum) is one of main food source with carbohydrates which is consumed by world people. The loss of wheat during storage is caused by pests attack. Flour beetle (Tribolium castaneum) is one of the main pests of wheat flour. Biological insectisidies is a solution to solve the attack of warehouse pests. The aim of research are to study the effectiveness of srikaya seeds on T. castaneum in wheat flour and to study the quality of wheat flour after the application srikaya seeds to T. castaneum. The research were be held in Pandan Rejo Village, Kebakkramat Sub-District, Karanganyar Regency on 105 asl altitude during September until October 2017. The research use Complete Randomized Design (CRD) with two factors of four repetitions. Dose treatment for Srikaya seeds consist of four levels of controls, 2.5 g/100 g wheat, 5 g/100 g wheat, and 10 g/100 g of wheat and the form of application consist of two kinds are 0.5 mm srikaya seed and 1 mm srikaya seed. Research variables which are observed were toxicity srikaya seed, imago mortality, moisture content, wheight shrinkage of wheat, color of wheat, and odor of wheat. The result show that LD50 of srikaya seed on a form 0.5 mm is 3.97 g/100 g wheat and form 1 mm is 4.70 g/100 g wheat. The application of the srikaya seed to minimize changes in quality wheat. The lowest shrinkage weight is 2.43 g and highest on the control of wheat color 5.805 g. control treatment from while to white murky scales (2). Scent control treatment of wheat does not become musty semlling scented (1).